(untitled) (Advancements in Homeopathic Research, 2023)
Warts are benign cutaneous and mucosal lesions. The human papillomavirus (HPV) causes warts, and there are over 100 different forms of HPV. HPV can be found anywhere. Although many Homoeopathic medicines may be found in therapeutics of warts but through this case , once again it has been proved that Homoeopathic medicines acts best when prescribed on the basis of individualisation that too quickly.